HAMBATAN IMPLEMENTASI KOMUNIKASI ILMIAH AKSES TERBUKA: TINJAUAN SISTEMATIS - Setio Devi, Katrin; Rahmi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2021)
Barriers to the implementation of open access globally need to be studied further using a systematic review. The purpose of this study is to look at the barriers from various countries in implementing open access. This study uses a systematic review method with a qualitative approach. The data collection method is in the form of planning, implementation, and synthesis of search results. This study uses Google Scholar to capture all research on implementing scientific communication with open access in the global realm. The search results on Google Scholar using Boolean logic found 273 articles. After the elimination process based on research objectives became 16 articles. This study shows that the biggest obstacle in implementing open access is the perception of the researchers (33.3%) which indicates that the quality of open access journals is less guaranteed, that is, many of them fall into the category of predatory journals. In addition, another obstacle identified was policy (25.6%). The government or stakeholders must make policies that regulate the standards for the quality of open access journals, the editorial board, and the time intervals for publishing journals. Other obstacles include financial factors where many researchers have minimal research funds but open access publications require large funds (23.1%), followed by copyright (10.3%) and language (7.7%) because not all researchers are fluent in English. The results of this study can be used as a reference for further research in assessing the obstacles that have also been happened in Indonesia.